Inventory of sustainable land management (SLM) practices for Uzbekistan’s marginal landscapes - Annex - Haddad, Mira; Lopez Montoya, Itzel; Akramkhanov, Akmal (2023)
Inventory of sustainable land management (SLM) practices for Uzbekistan’s marginal landscapes.